ANALISIS STATUS KUALITAS AIR ANAK- ANAK SUNGAI SINGINGI SEKITAR TAMBANG BATU BARA DI KUANTAN SINGINGI. - Noviawati Riza; Thamrin Thamrin; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2012)
Survay and analysis of water quality has been carried and in several rivers to know the effectof coal mines in the district of Singingi, Regency of Kuantan Singingi Riau Province on Aprilto November 2011. Water samples were collected from location of the mines effluent at Singingi River tributaries namely Sepuh river, Geringging river, Keruh river, Tapi river, flowin to Singingi river. The results of water quality compared with the Government Regulation no.82 year 2001 and refers to the Ministerial Decree. 115 year 2003 on water quality indexshown that Geringging river and Keruh river were heavily polluted, however Sepuh riverand Tapi river were moderate polluted.